2022
DOI: 10.1126/science.abo2523
|View full text |Cite
|
Sign up to set email alerts
|

Unadjuvanted intranasal spike vaccine elicits protective mucosal immunity against sarbecoviruses

Abstract: The SARS-CoV-2 pandemic has highlighted the need for vaccines that not only prevent disease, but also prevent transmission. Parenteral vaccines induce robust systemic immunity, but poor immunity at the respiratory mucosa. Here we describe the development of a vaccine strategy we term “prime and spike” that leverages existing immunity generated by primary vaccination (prime) to elicit mucosal immune memory within the respiratory tract using unadjuvanted intranasal spike boosters (spike). We show that prime and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(198 citation statements)
references
References 45 publications
8
145
3
Order By: Relevance
“…To date, intranasal and aerosolized vaccines have shown the most promise in doing so. 18 , 33 , 35 It is therefore essential to prioritise development of mucosal vaccines which can provide better protection against respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, intranasal and aerosolized vaccines have shown the most promise in doing so. 18 , 33 , 35 It is therefore essential to prioritise development of mucosal vaccines which can provide better protection against respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…administration in mice induce enhanced mucosal protection against SARS-CoV-2 variants. 18 This suggests that priming the nasal mucosa is required to induce effective local antibody responses that might provide enhanced immunity against current and future variants. However, the cross-reactivity of nasal antibody after infection with pre-Omicron virus is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, NP-specific serum IgG titers were similar in the BAL fluid between IM and IN vaccine delivery. Another group using an IM mRNA prime followed by a protein boost reported that IN protein delivery is particularly efficient in inducing IgA in BAL fluid ( 54 ). Although we were not able to detect NP-specific IgA, that might be consistent with the absence of vaccine-induced pulmonary T FH or due to technical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Laczkó and colleagues demonstrated the presence of activated CD69 + IV-neg T cells in the lung 10 days after IM mRNA-LNP vaccination, and a recent study from Mao et al. showed persistence of antigen-specific CD8 T cells in the lung for at least 56 days, raising the question of whether T RM are established ( 54 , 55 ). Here, we report the persistence of vaccine-elicited antigen-specific CD8 and CD4 T cells in the lung for at least 188 days after IM priming.…”
Section: Discussionmentioning
confidence: 99%
“…The FcRn-targeted nasal vaccine can be used for an unimmunized first dose or booster for those who have been immunized, even previously infected by SARS-CoV-2. The combination of mucosal and parenteral vaccines has been proven effective at mucosal entry against SARS-CoV-2 infections 7, 9, 44, 45 .…”
Section: Discussionmentioning
confidence: 99%